1995
DOI: 10.1017/s0252921100037878
|View full text |Cite
|
Sign up to set email alerts
|

A Nonlinear Pulsation Model for V652 Her

Abstract: Abstract. When compared with observation, stellar pulsation model predictions provide a test of stellar envelope opacities. Of specific interest, is the radially pulsating extreme helium star V652 Her for which luminosity and radial velocity observations are published. Nonlinear pulsation models of V652 Her, calculated using Opacity Project (OP) opacities, predict luminosity and radial velocity variations in close agreement with observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The obvious similarities between the two stars together with the theoretical work of Saio (1993, 1994) and Fadeyev & Lynas‐Gray (1996) and the observational data presented in this paper, strongly suggest that LSS 3184 is a radial pulsator. We have, therefore, attempted to apply the Balona (1977) method for stellar‐radius determination to our light, colour and velocity data.…”
Section: Radius Distance and Luminositysupporting
confidence: 75%
See 2 more Smart Citations
“…The obvious similarities between the two stars together with the theoretical work of Saio (1993, 1994) and Fadeyev & Lynas‐Gray (1996) and the observational data presented in this paper, strongly suggest that LSS 3184 is a radial pulsator. We have, therefore, attempted to apply the Balona (1977) method for stellar‐radius determination to our light, colour and velocity data.…”
Section: Radius Distance and Luminositysupporting
confidence: 75%
“…Many of these stars exhibit regular or ‘quasi’ regular variations, which are proven to result from stellar pulsation in some cases and suspected in others. Recent reviews of the subject can be found in the proceedings of the second conference on hydrogen‐deficient stars held in Bamberg in late 1995 (Jeffery & Heber 1996; see particularly Lawson & Kilkenny 1996, Saio 1996, Fadeyev 1996 in the conference proceedings and Fadeyev & Lynas‐Gray 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cause of variability is known as iron-group bump in the opacity (Saio 1995;Fadeyev & Lynas-Gray 1996), and the stars are definitely related to post-AGB stars.…”
Section: Introductionmentioning
confidence: 99%